Monitoring artisanal hilsa fishery for economic efficient fisheries policy (Bangladesh Journal of Zoology, 2015)
The hilsa shad (Tenualosa ilisha) fishery contributes to the largest single species fishery in Bangladesh. In this paper, a simple bio-economic year-class based model was developed from 1987 & 2007 fishing data to describe the fishery and examine its properties. With the help of this model, the optimum sustainable yield of the fishery was calculated and compared to the existing situation. The model was further used to locate socially and economically reasonable dynamic paths from the current situation to the optimal state. The results indicate that the fishing effort (measured in standardized boat units) required maintaining a maximum sustainable economic benefit is about one-third of the current fishing effort. At this sustainable fishing effort level, annual net economic benefits from the fishery amounted for closed to US$ 260 million compared to virtually nothing at present. The present value of the fishery along a moderate effort adjustment path to this long term equilibrium position was US$ 3,650 million at 6% rate of discount. The dynamic path that maximized the present value of the fishery involved quite dramatic effort reductions for the first two years. Such a path would probably increase the present value of the fishery by perhaps 8-10%.Bangladesh J. Zool. 43(1): 37-53, 2015